Application of green nanoparticles and nanocellulose in the production of smart textiles - Silva, Laryssa Pinheiro Costa (2022)
Textile activities cause major negative and often irreversible impacts on the environment. These impacts resulting from production run through the entire textile production chain: from the planting of cotton to the making of the garment. Along the textile production chain, environmental impacts involve soil contamination, consumption of water, energy, atmospheric emissions of pollutants and solid waste. On the other hand, consumers are increasingly demanding sustainable products and, following the emergence of the new coronavirus pandemic, are adopting stricter hygienic lifestyles. Cellulose is one of the most abundant and renewable organic raw materials in existence. In addition to its availability and sustainability, it has low cost and high strength. Through chemical, physical and enzymatic action, it is possible to transform cellulose into nanocellulose. Nanocellulose has advantages such as bioavailability, biocompatibility and high functionalization capacity. Here, we propose a sustainable route for the production of nanocellulose and direct our efforts towards the production of intelligent fabrics, with antimicrobian activity, using nanocellulose obtained from agribusiness residue (coconut fiber), functionalized with nanoparticles from green processes.